2021
DOI: 10.3390/ani11102914
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Broiler Requirements for Lysine and Arginine

Abstract: Six assays were conducted to investigate male and female broiler responses to standardized ileal digestible (SID) lysine (Lys) and arginine (Arg). Response data were modeled to estimate the efficiency of utilization (k) of both amino acids and adjust factorial models to predict bird intake for SID Lys and SID Arg. In each assay, 1280 Cobb 500® broilers (640 male and 640 female) were randomly assigned to one of sixteen dietary treatments with four replicates of 20 birds. Dietary treatments consisted of crescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similarly, during infections, the immune system is activated, which significantly affects the amino acid availability for muscle protein accretion, thus compromising growth. Arginine requirement will be increased during an active inflammatory response ( Rochell et al, 2017 ; Nogueira et al, 2021 ) indicated by a decreased plasma arginine concentration in infected birds. The increased demand for arginine during enteric infections such as coccidiosis might be due to its role in polyamine synthesis which is required for mucosal tissue repair ( Rochell et al, 2017 ).…”
Section: Arginine In Poultry Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, during infections, the immune system is activated, which significantly affects the amino acid availability for muscle protein accretion, thus compromising growth. Arginine requirement will be increased during an active inflammatory response ( Rochell et al, 2017 ; Nogueira et al, 2021 ) indicated by a decreased plasma arginine concentration in infected birds. The increased demand for arginine during enteric infections such as coccidiosis might be due to its role in polyamine synthesis which is required for mucosal tissue repair ( Rochell et al, 2017 ).…”
Section: Arginine In Poultry Productionmentioning
confidence: 99%
“…The increased demand for arginine during enteric infections such as coccidiosis might be due to its role in polyamine synthesis which is required for mucosal tissue repair ( Rochell et al, 2017 ). Thus, the body prioritizes the immune response over protein deposition during stress conditions ( Nogueira et al, 2021 ) reducing the metabolic availability of arginine and negatively impacting growth ( Allen and Fetterer, 2000 ). Similarly, during stress conditions, especially during heat stress, the sodium-dependent and sodium-independent uptake of arginine is depressed, increasing the arginine requirement in birds ( Khajali and Wideman, 2010 ).…”
Section: Arginine In Poultry Productionmentioning
confidence: 99%
“…Lysine ( Lys ) is defined as a basic essential amino acid whose carbon skeleton cannot be synthesized by poultry and therefore must be met through the diet for the maintenance and growth of poultry [ 6 ]. Lys is the second-most-limiting amino acid after methionine in corn–soybean meal-based diets for broilers.…”
Section: Introductionmentioning
confidence: 99%